UN SYSTEME D’INFORMATION URBAIN ET REGIONAL, APPLIQUE A LA REGION DE L’ESTRIE, PROVINCE DE QUEBEC / AN URBAN AND REGIONAL INFORMATION SYSTEM, AS APPLIED TO THE EASTERN TOWNSHIPS REGION, PROVINCE OF QUEBEC - Lacasse, Pierre (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2022)
see PDF